2020
DOI: 10.1186/s12942-020-00216-2
|View full text |Cite
|
Sign up to set email alerts
|

The association between spatial access to physical activity facilities within home and workplace neighborhoods and time spent on physical activities: evidence from Guangzhou, China

Abstract: Background: Urban residents from the developing world have increasingly adopted a sedentary lifestyle and spend less time on physical activities (PA). Previous studies on the association between PA facilities and individuals' PA levels are based on the assumption that individuals have opportunities to use PA facilities within neighborhoods all day long, ignoring the fact that their willingness and opportunities to use nearby facilities depend on how much discretionary time (any time when people have a choice w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…Apart from jobs, accessibility to essential goods and services is also a problem for lower income people [27,38,66,67,84,[87][88][89][90]. These services include health services, education, shopping and physical activity facilities.…”
Section: Limited Access To Essential Services and Facilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from jobs, accessibility to essential goods and services is also a problem for lower income people [27,38,66,67,84,[87][88][89][90]. These services include health services, education, shopping and physical activity facilities.…”
Section: Limited Access To Essential Services and Facilitiesmentioning
confidence: 99%
“…These services include health services, education, shopping and physical activity facilities. Longer travel times for these services may result in low satisfaction levels [66,89]. Among these services, poor access to medical facilities had a substantial impact on low-income households [37,39,90].…”
Section: Limited Access To Essential Services and Facilitiesmentioning
confidence: 99%
“…With increasing emphasis on health and well-being, the promotion of physical activity has aroused intense attention from the government, the public, and researchers. In this regard, a plethora of studies have reported that the availability and accessibility of sports and recreational services play a prominent role in physical activity attainment (Halonen et al, 2015;Heath et al, 2012;Humpel et al, 2002;Liu et al, 2019). In 2020, the World Health Organization (WHO) recommended at least 600 metabolic equivalent minutes of physical activity each week.…”
Section: Introductionmentioning
confidence: 99%
“…The association between specific environmental characteristics and physical activity in childhood has been extensively studied [ 11 , 12 , 13 , 14 ]. For example, an increased number of PA facilities has been shown to be associated with more time spent in MVPA [ 15 ]. Environments shown to support PA among children typically enable recreational activities, including parks, recreation fields, and green space (open land covered in grass or vegetation that could potentially be used for PA) [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%